2015
DOI: 10.1016/j.envres.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to phthalates, bisphenol A and perfluoroalkyl substances and cord blood levels of IgE, TSLP and IL-33

Abstract: The fetal time period is a critical window of immune system development and resulting heightened susceptibility to the adverse effects of environmental exposures. Epidemiologists and toxicologists have hypothesized that phthalates, bisphenol A (BPA) and perfluoroalkyl substance have immunotoxic properties. Immunotoxic effects of chemicals may manifest in an altered immune system profile at birth. Immunoglobulin E, thymic stromal lymphopoietin (TSLP), and interleukin-33 (IL-33) are integral in the etiology of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 79 publications
(90 reference statements)
3
51
1
1
Order By: Relevance
“…Recent studies found that maternal PFOA concentrations were inversely associated with current wheezing among Ukrainian but not in Greenlandic children aged 5–9 years (Smit et al 2015) and other types of maternal PFAS were inversely associated with allergic diseases among 4-year-old children (Goudarzi et al 2016). Several other analyses, however, showed no associations between pre-natal exposure to PFAS and cord blood IgE (Ashley-Martin et al 2015) or asthma and allergy in childhood (Wang et al 2011; Okada et al 2012; Granum et al 2013), which is in accordance with the current findings.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies found that maternal PFOA concentrations were inversely associated with current wheezing among Ukrainian but not in Greenlandic children aged 5–9 years (Smit et al 2015) and other types of maternal PFAS were inversely associated with allergic diseases among 4-year-old children (Goudarzi et al 2016). Several other analyses, however, showed no associations between pre-natal exposure to PFAS and cord blood IgE (Ashley-Martin et al 2015) or asthma and allergy in childhood (Wang et al 2011; Okada et al 2012; Granum et al 2013), which is in accordance with the current findings.…”
Section: Discussionsupporting
confidence: 91%
“…These recent publications include both epidemiological studies and experimental studies using animal models. Although the epidemiological studies published after 2012 (58) provide additional evidence of a potential association between BPA and immune effects, the available human studies corroborated EFSA’s conclusions as described above, indicating that a causal link cannot be identified from human studies due to limitations. For example, spot urinary BPA levels do not provide a reliable measure for exposure over time.…”
Section: Introductionsupporting
confidence: 62%
“…Contrary to this study, decreased IgE levels were reported with higher maternal PFOA concentrations in 18-month-old Japanese children, and no associations were observed between PFASs and food allergy, eczema or wheezing [61]. The Canadian MIREC birth cohort also found no association between 1st trimester pregnancy PFASs concentrations and cord-blood IgE levels [45]. Similarly, no associations were found between maternal prenatal PFASs concentrations and eczema/itchiness, wheeze, atopic eczema or asthma in a small sample (n = 99) of Norwegian children ages 1 to 3 years [58].…”
Section: Immunomodulatory Effectsmentioning
confidence: 75%
“…Thirteen studies reported on autoimmunity/hypersensitivity endpoints in eight prospective birth cohorts from Canada [45], Japan [61, 62, 63], Taiwan [65], Faroe Islands [57], Greenland, Ukraine [60], Norway [58] and from four cross-sectional studies in Taiwan [66] and the USA (NHANES) [4648]. Higher IgE levels in 2-year-old Taiwanese children were observed with higher cord blood PFOS and PFOA concentrations, but no associations were found for atopic dermatitis at the same age [65].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation